FUZZY OPTIMIZATION PROCESS OF DEEPENING DEEP WELLS - Horbiychuk, M. I.; Gumenyuk, T. V. (Radio Electronics, Computer Science, Control, 2015)
In the process of drilling deep wells for oil and gas it is important to make the correct choice of management influences – axial load on the bore bit and rotation frequency to obtain minimum cost of boring. Solving this problem involves the creation of an adequate mathematical model of the process of deepening wells and development of the methods for the identification of its parameters. The complexity of the problem is that the mechanical drilling process is stochastic, transient and is developing over time. This greatly complicates the determination of traditional methods of identification of a number of parameters that affect the process of the rock breaking. These parameters include the duration of descent-lifting operations, the values of which are affected not only by technological, technical, but also by subjective factors. For adequate reproduction of descent-lifting operations duration values uncertainty, they we proposed to consider them as fuzzy variables with certain membership functions. According to this premise, there was formulated the problem of fuzzy optimization of the deepening wells process and developed a method to solve it. The effectiveness of this method was confirmed on specific industrial data.